From 2D to 3D: Flood risk communication in a flood-prone neighborhood via dynamic, isometric street views - Jing Zhu; Debra F. Laefer; Raul P. Lejano; Peter Gmelch; Evan O'Keeffe; Kshitij Chandna (Progress in Disaster Science)
There is increasing evidence that climate change will lead to greater and more frequent extreme weather events, thus underscoring the importance of effectively communicating risks of record storm surges in coastal communities. This article reviews why risk communication often fails to convey the nature and risk of storm surge among the public and highlights the limitations of conventional (two-dimensional) storm surge flood maps. The research explores the potential of dynamic street-level, augmented scenes to increase the tangibility of these risks and foster a greater sense of agency among the public. The study focused on Sunset Park, a coastal community in southwest Brooklyn that is vulnerable to storm surges and flooding. Two different representations of flooding corresponding to a category three hurricane scenario were prepared: (1) a conventional two-dimensional flood map (“2D” control group) and (2) a, dynamic, street view simulation (“3D” test group). The street view simulations were found to be (1) more effective in conveying the magnitude of flooding and evacuation challenges, (2) easier to use for judging flood water depth (even without a flood depth legend), (3) capable of generating stronger emotional responses, and (4) perceived as more authoritative.in nature.